Wind tunnel study of airflow recovery on the lee side of single plants - Cheng, Hong; Zhang, Kaidi; Liu, Chenchen; Zou, Xueyong; Kang, Liqiang; Chen, Tianle; He, Weiwei; Fang, Yi (Agricultural and forest meteorology, 2018)
•Airflow fields simulation in the lee side of plants with different characteristics.•A new model of the airflow recovery in the lee side of plants.•The parameters for the new model determined by plant characteristics parameters. Plants play an important role on reducing the soil erosion rate and preventing blown sand motion. The primary cause is the airflow change around the plant, especially for the lee side of plants. Although scientist have researched this topic, significant problems remain concerning airflow around plants. Therefore, we conducted a series of wind tunnel experiments to simulate average airflow speed and turbulence intensities on the lee side of eight single plants with varying characteristics under different shear velocities by utilizing a hot film anemometer. We come to the following conclusions: (1) Variation in the airflow speed along the plant downwind direction is related to the porosity and the height-to-width ratio (H/W). The weakened degree of wind speed decreases with plant porosity, and the minimum wind speeds (umin) at different heights are different for different H/W. For large H/W (H/W ≥ 2), the values of umin appear at the location of 1 H in the lee side of the plant, while the location where umin occurs for small H/W (H/W ≤ 0.5) is related to the height. The location most frequently occurs between 3 h and 5 h. (2) This paper presented a modification for relaxation equation to express airflow recovery on the lee side of plant and developed the relationships of the minimal wind speed (umin), occurring lee-side location (x0), and the characteristic length (l) in this modified relation equation, with different plant characteristic. The value of umin increases with the plant porosity (β) in a linear function of umin = 0.0183β-0.65 and the location (x0) where umin occurs and the characteristic length for wind speed recovery are proportional to the reciprocal of the ratio of plant height-to-width. Their relationships can be expressed as x0 = 1.68(H/W)−1 and l = 5.30(H/W)−1, respectively. (3) The turbulence intensity downwind direction of the plant is several times the intensity of the incoming flow, and the peak turbulence intensity can reach up to 50%. The more significantly the wind speed weakens, the more significant the increase in the turbulence intensity. The standard deviation of the wind speed varies slightly.